Microbial enzymes: from earth to space - Raja Abd. Rahman, Raja Noor Zaliha (Universiti Putra Malaysia Press, 2009)

(untitled)
Biotechnology can provide an unlimited and pure source of enzymes as an alternative to the harsh chemicals traditionally used in industry for accelerating chemical reactions. Enzymes are found in naturally occurring microorganisms, such as bacteria, fungi and yeast, all of which may or may not be genetically modified. Hydrolytic enzymes, such as lipases and proteases are much sought after as the biocatalysts of the future. Proteases have been widely used in industry and there is always scope for new enzymes to be utilized in existing applications as well as new ones. Lipases on the other hand, are projected to have exciting potential in the advancement of the bioprocessing industry in particular oleochemicals. Thermostable enzymes are always sought by the industries while solvent tolerant enzymes are becoming the vogue in view of their ability to function in low aqueous medium, suitable for synthetic reactions. Advances in science and technology have allowed researchers to improve enzymes either through modifications of enzyme producing microorganisms, or via direct changes to the enzymes themselves. By studying the relations between the structure of a protein and how it functions, methods to improve and engineer enzymes can be developed. One of the most widely used methods in studying protein structures is crystallography which can provide an insight into the protein structures and functions from global folds to the atomic details of bonding. The crystals are analyzed by x-ray diffraction to determine their structures, but this procedure is only possible for large and relatively pure proteins. As protein crystals are fragile, it is difficult for some proteins to grow adequately large or to obtain perfect protein crystals in Earth-based laboratories. The influence of gravity on Earth distorts the shape of the crystals resulting in imperfections in the structures. Microgravity can provide an ideal environment for the growth of crystals. This is due to the fact that in a microgravity environment of space there are no gravity-induced effects such as sedimentation and convection that can disrupt the growth of these fragile protein crystals; thereby increasing the probability of growing larger, more perfect crystals. Crystals grown in microgravity generally have improved morphology, larger volume, better optical properties and higher diffraction limit compared with Earth-grown crystals.